MENTORING CLASS PROGRAM FOR PROBLEM-SOLVING SUPPORT IN PESANTREN-BASED JUNIOR HIGH SCHOOL - Tri Apriliani; Nadia Rafiah Nawa Kartika (SUJANA: Education and Learning Review, 2025)
This qualitative case study examined the implementation of the Mentoring Class program as a problem-solving support approach for students at SMP Bumi Cendekia Yogyakarta, a pesantren-based junior high school in Indonesia. Pesantren students face unique challenges including dual academic burdens, cultural adjustment difficulties, and distance from family support systems. Data were collected through non-participant observation, semi-structured interviews with school administrators, mentor teachers, and student mentees, and documentation analysis. Findings revealed that the program effectively supported student problem-solving development through structured weekly sessions, grade-appropriate materials aligned with institutional values, and small group configurations of 11-12 students per mentor. The quality of mentor-mentee relationships, characterized by trust and regular interaction, emerged as a critical factor in program success. Students demonstrated progressive development from external dependence on mentors toward internal self-regulation in problem solving over the academic year. Additionally, the group mentoring format fostered peer solidarity and reduced feelings of homesickness and isolation among students from diverse regional backgrounds. This study extends existing mentoring literature by documenting effective adaptation of structured mentoring interventions to pesantren-based junior high school contexts, validating the role of supportive relationships in addressing boarding school challenges, and revealing temporal progression in self-regulated learning development. Findings contribute valuable insights for educational practitioners seeking to implement support mechanisms in boarding school environments.